2022
DOI: 10.7150/ijms.69868
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin Polymorphisms, Lifestyle Risk Factors and Risk of Oral Squamous Cell Carcinoma in a Cohort of Taiwanese Males

Abstract: Oral cancer is the eighth greatest generally diagnosed cancer amongst males worldwide and the fourth most generally malignancy amongst Taiwanese males. The pro-inflammatory adipocytokine visfatin promotes tumor growth. Elevated plasma visfatin levels have been identified in patients with oral squamous cell carcinoma (OSCC), although the biological mechanisms underlying the involvement of visfatin in the pathogenesis of OSCC are not well understood. Moreover, no information is available regarding associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…In our study, neither visfatin SNPs rs4730153 nor rs2110385 were associated with particular clinicopathologic characteristics in LUAD. However, our previous study reported that the SNP rs4730153 GA genotype was associated with lymph node metastasis in OSCC betel nut chewers, whereas the SNPs rs2110385 and rs61330082 had no relation to OSCC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In our study, neither visfatin SNPs rs4730153 nor rs2110385 were associated with particular clinicopathologic characteristics in LUAD. However, our previous study reported that the SNP rs4730153 GA genotype was associated with lymph node metastasis in OSCC betel nut chewers, whereas the SNPs rs2110385 and rs61330082 had no relation to OSCC [ 23 ].…”
Section: Discussionmentioning
confidence: 99%
“…The visfatin SNP rs11977021 has been investigated in other cancers. Our previous investigation found that having the visfatin SNP rs11977021 and the CT + TT genotypes was associated with a lower risk of developing OSCC compared with those with the CC genotype at the same SNP [ 23 ]. In contrast, in another study involving patients with hepatitis B virus (HBV) infection, there was no significant association between visfatin rs11977021 and the risk of developing HBV-related hepatocellular carcinoma (HBV-HCC) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations